(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
The spotted wing drosophila Drosophila suzukii Matsumura (Diptera: Drosophilidae) is an invasive pest originating from Southeast Asia. It was detected for the first time in Europe in 2008 (Spain and Italy) and subsequently in other European countries. It is a highly polyphagous pest that infests healthy, ripening fruit and presents a serious threat to fruit production, particularly of soft skinned fruit. In the first half of October 2013, a new fruit fly species was unexpectedly detected in Tephri traps baited with the three-component female-biased attractant BioLure that is regularly used for monitoring the Mediterranean fruit fly Ceratitis capitata Wiedem. (Diptera: Tephritidae) in Montenegro. Brief visual inspection identified the new species as the spotted wing drosophila D. suzukii. The pest was first recorded in several localities on the Montenegrin seacoast around Boka Kotor Bay. After the finding, all Drosophila specimens were collected from traps for further laboratory observation. A quick follow-up monitoring of other Tephri traps was carried out within the next few days on the rest of the seacoast (localities from Tivat to Ulcinj). Additionally, Tephri traps were set up around Lake Skadar and in the city of Podgorica, as well as on fresh fruit markets in Podgorica. The results of this preliminary study showed that D. suzukii was present in all surveyed locations and adults were captured until late December. Both sexes were found in traps with BioLure. Our data show that D. suzukii is present in southern parts of Montenegro and there is a serious threat of its further spreading, particularly towards northern parts of the country where the main raspberry and blueberry production is placed. The results also show that Tephri traps baited with BioLure can be used for detection and monitoring of spotted wing drosophila.